2012
DOI: 10.1063/1.3693330
|View full text |Cite
|
Sign up to set email alerts
|

Ionic force field optimization based on single-ion and ion-pair solvation properties: Going beyond standard mixing rules

Abstract: Using molecular dynamics (MD) simulations in conjunction with the SPC/E water model, we optimize ionic force-field parameters for seven different halide and alkali ions, considering a total of eight ion-pairs. Our strategy is based on simultaneous optimizing single-ion and ion-pair properties, i.e., we first fix ion-water parameters based on single-ion solvation free energies, and in a second step determine the cation-anion interaction parameters (traditionally given by mixing or combination rules) based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
218
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(237 citation statements)
references
References 70 publications
8
218
1
Order By: Relevance
“…13,14 More recently, force fields for aqueous solutions of alkali, alkali-earth and halide ions were developed that also show reasonable anion-cation interactions. They are thus able to reproduce experimental osmotic pressures or solution activities at salt concentrations below 1 M, [15][16][17][18][19] and in a few cases up to much higher concentrations. 20 Simulations based on these force fields have already offered unprecedented insight into the molecular scale origin of ion-specific effects in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 More recently, force fields for aqueous solutions of alkali, alkali-earth and halide ions were developed that also show reasonable anion-cation interactions. They are thus able to reproduce experimental osmotic pressures or solution activities at salt concentrations below 1 M, [15][16][17][18][19] and in a few cases up to much higher concentrations. 20 Simulations based on these force fields have already offered unprecedented insight into the molecular scale origin of ion-specific effects in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Mouka et al, 107 they found the parameter set from Joung and Cheatham 18 (the JC parameter set herein) and the parameter set 5b from Horinek et al53 (the H2 parameter set herein, the values were adopted using Lorentz-Bertholet (LB) combining rules and are shown inTable SI.8) are the best among thirteen different parameter sets for simulating NaCl solutions with the SPC/E water model. In the work of Fyta and Netz, they re-optimized the mixing rules of the ion pairs to reproduce the activity derivative of several different kinds of ion solutions 108. They found it was hard to reproduce the experimental activity derivatives of the NaF, KF, NaI and CsI ion solutions.When compared to the values obtained using the unoptimized LB combining rules, they found that a larger ε ij value for NaF, a larger R min,ij value for KF, and a smaller ε ij value for NaI and CsI were necessary to reproduce the experimental activity derivatives.In the present work, we have carried out simulations on NaCl, KCl, NaF, KF, NaI and CsI ion solutions at a concentration of ~0.30 M. The SPC/E water model was used in these simulations.…”
mentioning
confidence: 98%
“…To achieve such agreement with experiment, in CHARMM36 the Lennard-Jones parameters characterizing the interaction of Na + with selected groups in the phospholipid are not calculated following the standard arithmetic combining rules, but they are determined specifically for each atom pair (NBFIX) 30 . The need for a specific description of certain pair interactions shows the limitation of point charge force fields, which cannot account for charge transfer or polarization effects 31 .…”
Section: System Setup and Equilibrationmentioning
confidence: 99%